Modal analysis of industrial fluid structure systems with symmetric formulations in a finite element code - Sigrist, Jean-François (European Journal of Computational Mechanics, 2007)
The present paper deals with numerical developments performed in the finite element code ANSYS in order to implement coupled fluid structure formulations using symmetric matrices. The so-called (u, p, φ) formulation with mass and stiffness coupling is developed in the ANSYS code, enhancing the modeling possibilities of the existing fluid elements. Theoretical bases of the formulation are first exposed, test-cases and industrial application are then proposed. It is shown that computing times are decreased by 90% using a symmetric formulation instead of a non-symmetric one, allowing modal analysis of complex structures with fluid coupling for industrial purposes.